A Pedagogia Histórico-Crítica no contexto da nova política curricular: um estudo sobre o ensino de química na Base Nacional Comum Curricular e no Currículo de Referência de Mato Grosso do Sul - Marcos Geraldo Vieira (2024)
This work is based on the recognition that the current Brazilian school curriculum, that is, the National Common Curricular Base (BNCC), and also the Mato Grosso do Sul Reference Curriculum (CRMS), are State policies whose implementations take place within the scope of the neoliberal political and economic agenda. The aim is to analyze the characterization of these educational policies regarding the teaching of Chemistry for the High School stage, as well as their relationship (approximation/distance) with Historical-Critical Pedagogy (PHC). The research is based on the critical perspective, in order to analyze the object in light of the material, social and historical reality, using the documentary analysis technique. It is based on research by important authors in the field, such as: Antunes (2009); Antunes and Pinto (2017); Jesus (1989); Giareta (2021a; 2021b); Silva (2016; 2020); Zank and Malanchen (2020); Neves (2005); Gramsci (1982; 1968); Saviani (2011; 2012a; 2012b; 2012c; 2019, 2020, 2021); Duarte (2012; 2020); Cury, Reis and Zanardi (2018); Del Roio (2018); Laval (2004); Mèszàros (2008), among others, who offer their theoretical contributions to elucidate the research theme. The research indicates that the BNCC and CRMS, from the perspective of teaching Chemistry, have theoretical and methodological matrices based on the Pedagogy of Competencies. In addition, they are deeply marked by the hegemonic disciplines of neoliberal sociability. The curricular organization centered on skills and competencies tends to deepen class divisions and restrict access to elaborated knowledge and culture, significantly impacting students from lower classes. Thus, they present several contradictions and distances in relation to Historical-Critical Pedagogy.